THE STRENGTH OF TRANSVERS ACRYLIC RESIN WITH GLASS FIBER SOAKED IN TEA - Sujati, Sujati (Journal of Vocational Health Studies, 2021)
Background: In acrylic removable dentures, brokenness often occurs in the midline region of the maxilla. Resistance to fracture depends on the physical properties of the material namely the transverse strength. This can be prevented by the addition of glass fibers. Tea is consumed by many people, acrylic resin dipped in steeping tea will reduce the strength of acrylic resin. How the physical properties of acrylic resin are modified by the addition of glass fiber effect when immersed in a tea solution. Purpose: This study was to determine the strength of transverse acrylic resin with the addition of glass fibers soaked in tea. Method: Rectangular acrylic resin with a size of 10 x 65 x 2.5 mm. The number of samples is 24. divided into 4 groups. namely 2 groups without glass fiber and 2 groups with glass fiber. The sample is measured by transverse strength using an autograph (Shimadzu) tool, then data is analyzed using ANOVA. Result: Acrylic resin without glass fiber immersed in tea solution decreases its transverse strength. while the acrylic resin was given glass fiber the strength value of the transversion does not differ significantly either soaked or not. Conclusion: Acrylic resin which is given glass fiber and soaked in tea does not reduce the strength of the transversion. This is due to the glass fiber filling the cavity in the acrylic resin.